A new species of Dibamus (Squamata: Dibamidae) from Peninsular Malaysia - Das, I.; Norsham, Yaakob (National University of Singapore, 2003)
A new species of Dibamus is described from Batu Gua Madu, Kelantan State, northern Peninsular Malaysia. The new species, Dibamus booliati, differs from its congeners in the following combination of characters: SVL to 102.7 mm; TL to 9.7 mm; TL/SVL% 9.4-13.0; postocular single; rostral suture absent; interparietal posteriorly bordered by four slightly smaller nuchal scales; supralabial one, bordering ocular ventrally; scales bordering posterior edge of infralabial after postmental three; ventrals 180-209; subcaudals 24-39; presacral vertebrae 113-120; postsacral vertebrae 11-25; and dorsum and venter brown with a pale neck band.